Effectiveness of the Implementation of an Innovative Problem-Based Learning (PBL) Model Based on TPACK to Enhance Student Engagement and Learning Outcomes in IPAS - Lailatul Zahroh; Sukendro; Indryani (Postgraduate, University of Mataram, 2025)
This study aims to analyze the effectiveness of implementing an innovative Problem-Based Learning (PBL) model based on Technological Pedagogical and Content Knowledge (TPACK)—a model never used before—in an effort to increase both student engagement and learning outcomes in Natural and Social Sciences (IPAS) among fourth-grade students at SD Negeri Sentang. The study was conducted in the fourth-grade class of SD Negeri Sentang during the 2024/2025 academic year and employed a classroom action research (PTK) design. The population and sample consisted of 12 fourth-grade students (6 boys and 6 girls). The research instruments included observation sheets, field notes, and a test result assessment format for cognitive learning outcomes. Both quantitative and qualitative data were collected through observations, interviews, and documentation. Quantitative analysis was used to evaluate observation and test results, while qualitative analysis was employed to assess student interview data. This study was conducted as an effort to create a technology-integrated learning environment that enhances engagement—focusing on 21st-century skills (communicative, collaborative, critical thinking, collaboration)—and improves student learning outcomes. The findings indicate that the innovative PBL model based on TPACK significantly improved student engagement and learning outcomes, as evidenced by observations, interviews, and test results. The study recommends adopting the innovative PBL model that leverages technology to achieve better educational outcomes.